2020
DOI: 10.3390/app10144940
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation, Optical and Emission Performance of Zinc Silicate Glass-Ceramics Phosphor Derived from the ZnO–B2O3–SLS Glass System

Abstract: A new transparent zinc silicate glass-ceramic was derived from the 55ZnO–5B2O3–40SLS glass system via a controlled heat-treatment method. The precursor glass sample was placed through the heat-treatment process at different temperatures to study the progress in phase transformation, optical performance and emission intensity of the zinc silicate glass-ceramics. For this project, material characterization was measured through several tests using densimeter and linear shrinkage measurement, X-ray diffraction (XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Meanwhile, the other study provided a significant finding of blue emission pronounced in ZBS samples due to the ZnO crystalline phase [49]. It was rarely found in other zinc silicate-based host matrix as usually, green and yellow were commonly found in general [50,51]. Meanwhile, an intensified red band prominently occurred at 643 nm is due to the structural defect in ZnO that appeared in the form of oxygen vacancy and zinc interstitial [16,40], which was also found earlier in [52].…”
Section: Optical Characterization Of the Zno-b 2 O 3 -Sio 2 (Zbs) Glamentioning
confidence: 66%
“…Meanwhile, the other study provided a significant finding of blue emission pronounced in ZBS samples due to the ZnO crystalline phase [49]. It was rarely found in other zinc silicate-based host matrix as usually, green and yellow were commonly found in general [50,51]. Meanwhile, an intensified red band prominently occurred at 643 nm is due to the structural defect in ZnO that appeared in the form of oxygen vacancy and zinc interstitial [16,40], which was also found earlier in [52].…”
Section: Optical Characterization Of the Zno-b 2 O 3 -Sio 2 (Zbs) Glamentioning
confidence: 66%
“…37-1485). Also, it had been found that the improvement of the sintering period up to 10 hours, led to the progress of diffraction peak intensity of the crystal phase [8]. This finding can be corroborated by the values for full width at half maxima (FWHM) obtained from the X'pert highscore software was found to be decreased with the progression of the sintering duration from 0.5196, 0.2273, and 0.1624, respectively.…”
Section: Fig 2 Ftir Absorbance Spectra Of Heat-treated Rice Husk Ash ...mentioning
confidence: 70%
“…α-Zn 2 SiO 4 with polymorph of zinc orthosilicate as the most commonly found crystalline phase in Zn 2 SiO 4 glass-ceramics. Significant attention has been put on the fabrication of Zn 2 SiO 4 as it offers excellent glass transparency [8] and substantial fluorescence characteristics [9]. Optically, its wide bandgap has made it attentively produced as light-emitting diodes [7], laser diodes [10], display panel [11], and cathode-ray phosphor [12].…”
Section: Introductionmentioning
confidence: 99%
“…As the WGCs are very common with green emission of 522 nm, it is in line with the XRD pattern that Dy 3+ :WGC0 and Dy 3+ :WGC6 have not grown the willemite crystals. [26] Intensity (a.u. )…”
Section: Resultsmentioning
confidence: 99%